Changes in Systolic Blood Pressure over Time in Healthy Cats and Cats with Chronic Kidney Disease. (27th April 2015) - Bijsmans, E.S.; Jepson, R.E.; Chang, Y.M.; Syme, H.M.; Elliott, J.
<x xml:space="preserve">Abstract</x> Background Hypertension is a common problem in older cats, most often associated with chronic kidney disease (CKD). Cross‐sectional studies have suggested that blood pressure in cats increases with age. Hypothesis/Objectives To determine whether blood pressure in cats increases with age and whether this occurs independently of the presence of CKD. To investigate risk factors for developing hypertension. Animals/Subjects Two hundred and sixty‐five cats with CKD and 133 healthy cats ≥9 years were retrospectively identified. Methods Four groups were created according to status at initial evaluation (CKD or healthy) and blood pressure at the last included visit (normotensive [NT] or developed hypertension [DH]): Healthy‐NT, Healthy‐DH, CKD‐NT and CKD‐DH. Systolic blood pressure (SBP) over time slopes were compared with 0 and between groups. Risk factors for the development of hypertension were investigated, and associations of biochemical and clinical variables with SBP were examined. Results Cats that were hypertensive at CKD diagnosis (n = 105) were not included in further analyses. Twenty‐seven cats with CKD and 9 healthy cats developed hypertension ≥3 months after diagnosis of CKD or their first visit. Systolic blood pressure significantly increased with age in all cats (P < .001). Healthy cats were at less risk than cats with CKD to become hypertensive (hazard ratio 0.2, P < .001), with creatinine being an independent risk factor for the development of hypertension. Conclusions and Clinical Importance The high prevalence of hypertension in azotemic cats in this study shows the importance of monitoring of SBP in elderly cats, and in particular in cats with CKD.